Association between the composite dietary antioxidant index and all-cause mortality in individuals with osteoarthritis via NHANES data - Wei Jiang; Jie Li; Haopeng Li (Scientific Reports)
Abstract The impact of antioxidant intake on the prognosis of osteoarthritis (OA) patients remains unclear. The aim of this study was to investigate the relationship between the composite dietary antioxidant index (CDAI) and all-cause mortality in OA patients. A total of 35,590 participants with OA from the National Health and Nutrition Examination Survey (1999–2020) were included in this study. We analysed the associations between the CDAI and the risk of all-cause mortality in OA patients via a multivariate Cox regression model. Restricted cubic spline regression was used to investigate the dose–response associations between the CDAI and mortality. We also conducted stratified analyses and interaction tests to explore underlying effect modification. After multivariable adjustment, each one-unit increase in the CDAI was associated with a 2.1% reduction in the risk of mortality. Compared with those in the low CDAI group, the multivariate-adjusted hazard ratios (HRs) for mortality for patients in the high CDAI group were lower [Model 1 (HR 0.648, 95% CI 0.557–0.754), Model 2 (HR 0.739, 95% CI 0.627–0.871), and Model 3 (HR 0.788, 95% CI 0.661–0.941)]. We observed a negative nonlinear relationship between the CDAI and all-cause mortality (P < 0.05). Stratification analyses and interaction tests confirmed the robustness of the results. We found a negative nonlinear relationship between the CDAI and all-cause mortality in OA patients. A higher CDAI was significantly associated with a lower risk of mortality. These results highlight the potential advantages of monitoring and evaluating the CDAI status in preventing mortality among patients with OA.